Pengembangan Sikap Profesional Guru Dalam Meningkatkan Kompetensi Pedagogik, Profesional, Kepribadian, Dan Sosial - Fitrah, Anggun Diva; Azizah, Amaliyah Nur; Loviana, Lutfi Fadila; Rofiqoh, Vivi Fadhilatul; Sutarto, Sutarto (Jurnal Ilmiah Wahana Pendidikan, 2025)
professionalism of teachers is the key to achieving this goal. It's a paper that discusses the importance of improving teacher professionalism, the factors that influence the professionalism of teachers, and The techniques that might be applied to enhance teacher professionalization. The study uses the methodology of literature studies to define teacher professionalism as the ability and skills that teachers possess in performing their roles and obligations successfully and efficiently in order to achieve educational objectives. The four main pillars of teacher professionalism are pedagogical, professional, social, and personal competence. A number of other variables, including resource availability, school support, teacher self-motivation, and governmental legislation, can have an impact on the development of teacher professionalism. To enhance teacher professionalism, broad strategies such as training, seminars, workshops, and the development of teacher learning communities areneeded